Impact of early intervention and disease modification in patients with predementia Alzheimer’s disease: a Markov model simulation - Budd D; Burns LC; Guo Z; L’Italien G; Lapuerta P (Dove Medical Press, 2011)
David Budd1, Leah C Burns2, Zhenchao Guo2, Gilbert L’Italien2,3, Pablo Lapuerta11Bristol-Myers Squibb, Princeton, NJ, USA; 2Bristol-Myers Squibb, Wallingford, CT, USA; 3Yale University School of Medicine, New Haven, CT, USABackground: Early screenings involving biomarkers and use of potential disease-modifying therapies (DMTs) may have significant humanistic implications for treatment strategies in Alzheimer’s disease.Methods: Markov models simulated transitions of patient cohorts beginning in predementia, a hypothetical early stage of Alzheimer’s disease marked by objective cognitive impairment/memory complaints without functional impairment, and followed for 10 years. Hypothetical cohorts of 10,000 patients included those who were treated with standard of care (donepezil) upon reaching mild–moderate Alzheimer’s disease, a DMT in predementia, and a DMT in mild-moderate Alzheimer’s disease. Transition probabilities were based on data from the Alzheimer’s Disease Neuroimaging Initiative and published clinical data, and estimated for the hypothetical DMT. In each disease stage (predementia, mild, moderate, or severe), time was computed and costs were estimated using literature review and published data, and published data provided mortality rates. The impact of screening was evaluated using positive predictive value (patients identified as predementia truly at risk for transition to dementia).Results: Earlier treatment yielded modest gains in total life-years; however, the distribution was skewed towards milder disease. Assuming a 25% reduction in the annual risk of progression, treating predementia patients with DMT increased life-years in predementia to mild states on average from 3.2 to 4.2, while life-years spent in moderate-to-severe Alzheimer’s disease decreased from 2.6 to 2.2. Average time in the community increased from 4.4 to 5.4 years, while time in long-term care declined from 1.3 to 0.9 years. This impact grows as the advantage of the novel agent increases. Screening accuracy had significant implications for cost-effectiveness.Conclusion: If screening can accurately identify predementia patients at risk for progression, earlier treatment with DMTs has the potential benefit to patients of prolonging time in milder disease, reducing time spent with more severe disease, increasing time in the community, and reducing time in long-term care.Keywords: Alzheimer’s disease, Markov model, disease-modifying therapy, donepezil, standard of care, predementia